USE OF ESTRUS INDUCTION STRATEGY IN TRUE ANESTRUS BUFFALO FOR REDUCING NON-PRODUCTIVE PERIOD - MUNGAD, KS; PATEL, JA; DHAMI, AJ; HADIYA, KK; BORKHATARIYA, DN; SARVAIYA, NP (The Indian Journal of Animal Reproduction, 2022)
True anestrus buffalo were subjected to three hormone protocols (Ovsynch, Heatsynch and Triu-B protocol) during summer and winter season for the induction of synchronized estrus followed by fixed-time AI (n=12 in each group). Estrus induction response was similar (75.0-91.6%, p>0.05) between protocols during summer and winter. Overall conception rate in response to AI at induced estrus and at subsequent two spontaneous estruses was between 25.0-33.3% in summer and 50.0 - 58.3% during winter. In comparison, 8.3% and 25.0% untreated control buffalo exhibited spontaneous estrus and conceived during summer and winter season, respectively. Plasma progesterone profile confirmed anestrus status of buffalo recruited in the study as well as the success of hormone protocols and subsequent pregnancy status (p
Keywords: Buffalo; Fertility; Estrus synchronization; Season; Progesterone